Magnetic design and modelling of a 14 mm‐period prototype superconducting undulator. (16th February 2017) - Mishra, G.; Gehlot, Mona; Sharma, Geetanjali; Trillaud, Frederic
Abstract : The magnetic design of a ten‐period (each period 14 mm) prototype superconducting undulator is reported using RADIA, and the results of magnetic flux density modelling are presented in an analytical formula. Abstract : The magnetic design of a ten‐period (each period 14 mm) prototype superconducting undulator is reported using RADIA . The results of modelling the magnetic flux density are presented in an analytical formula. The dependence of the field integrals and phase error on the current density and undulator gap has been calculated, and temperature curves are determined for the models and are compared with earlier reported Moser–Rossmanith fits.